2016
DOI: 10.1002/mop.30308
|View full text |Cite
|
Sign up to set email alerts
|

High‐gain wide‐bandwidth low noise amplifier multi‐chip waveguide module at V‐band

Abstract: A low‐noise, high‐gain, wide‐bandwidth multi‐chip module has been developed at V‐Band with WR‐15 waveguide interface using commercial‐off‐the‐shelf (COTS) Low Noise Amplifier (LNA) Monolithic Millimeter‐wave Integrated Circuits (MMICs). Waveguide module design ensures there is minimal impact on noise figure and gain of MMICs due to integration on the module and it is rugged to sustain impact of fabrication/assembly tolerances. The realized six‐stage LNA module has small‐signal gain of 32–35 dB and room tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…10 Furthermore, shunt capacitors (C g1 , C d1 , C g2 , and C d2 ) were utilized near the choke inductors to filter the unwanted oscillation phenomena on the DC bias lines. 10 MMIC LNA was designed and simulated in ADS Momentum simulator. Simulated stability results are given in Figure 3.…”
Section: Mmic Lna Designmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Furthermore, shunt capacitors (C g1 , C d1 , C g2 , and C d2 ) were utilized near the choke inductors to filter the unwanted oscillation phenomena on the DC bias lines. 10 MMIC LNA was designed and simulated in ADS Momentum simulator. Simulated stability results are given in Figure 3.…”
Section: Mmic Lna Designmentioning
confidence: 99%
“…Moreover, the transistors were matched to the Γ opt to achieve the minimum NF. Furthermore, DC biases were supplied on a choke inductor ( L g1 , L g2 , L g3 , and L g4 ) to decouple the high frequency transmission to the DC bias line and the serially connected capacitors (C 1 and C 2 ) were utilized in the input and output ports to prevent the external DC bypass capacitor usage in the module level 10 . Furthermore, shunt capacitors (C g1 , C d1 , C g2 , and C d2 ) were utilized near the choke inductors to filter the unwanted oscillation phenomena on the DC bias lines 10 .…”
Section: Rf Front‐end Module Designmentioning
confidence: 99%
“…The research of waveguide probes and bonding wires have been extensively reported. [2][3][4][5][6][7][8] However, as operating frequencies increase, bonding wires will cause considerable loss due to the parasitic inductance. 9 Although this effect can be reduced by using multiple wires or shortening the wires, it is difficulty to apply them to sub-millimeter wave and terahertz devices due to the small circuit dimension.…”
Section: Introductionmentioning
confidence: 99%
“…At present, waveguides are widely used due to its low transmission loss, and a popular packaging technology to achieve MMIC‐to‐waveguide transition is based on waveguide probe and wire‐bonding technologies. The research of waveguide probes and bonding wires have been extensively reported 2–8 . However, as operating frequencies increase, bonding wires will cause considerable loss due to the parasitic inductance 9 .…”
Section: Introductionmentioning
confidence: 99%